The effects of a place-based tax cut and minimum wage increase on labor market outcomes - Raymundo M. Campos-Vázquez; Victor Delgado; Alexis Rodas (IZA Journal of Labor Policy, 2020)
The benefits of place-based policies are still under debate. In this study, we analyze what is probably one of the boldest interventions in the recent history of Mexico and the rest of the world: the Northern Border Free Zone (NBFZ). Launched in January 2019, this program doubles the minimum wage and substantially lowers taxes in 43 municipalities along the border with the United States, aiming to improve living standards for low-wage workers and foster economic activity within the region. Given the unique features of the NBFZ, we estimate its short-run effects on labor outcomes: employment, wages, and formality. Our primary identification strategy follows a synthetic control method employing monthly administrative data at the municipality level for the period 2015-2019. Using administrative data for formal employment, we find that the policy substantially increased labor income in the NBFZ by approximately 9% over the control municipalities. The results for employment are less clear. Formal employment showed 1.6% less growth in the NBFZ than in the control municipalities, but the estimate is imprecise and we cannot reject a null impact of the program on employment. These results are robust to alternative control groups, including metropolitan areas in the United States. We also use the labor force survey to estimate the effects on formality at the individual level and find results closer to a null effect. These two results suggest that the NBFZ did not substantially affect employment, and the intersection of confidence intervals for the two estimates implies a maximum loss of employment of approximately 24,000 jobs.
Keywords: H30; J20; J30; O54; 330; minimum wage; taxes; place-based policy; employment; Mexico